PID Control for Electric Vehicles Subject to Control and Speed Signal Constraints - Amanda Danielle O. da S. Dantas; André Felipe O. de A. Dantas; João Tiago L. S. Campos; Domingos L. de Almeida Neto; Carlos Eduardo T. Dórea (Journal of Control Science and Engineering)
A PID control for electric vehicles subject to input armature voltage and angular velocity signal constraints is proposed. A PID controller for a vehicle DC motor with a separately excited field winding considering the field current constant was tuned using controlled invariant set and multiparametric programming concepts to consider the physical motor constraints as angular velocity and input armature voltage. Additionally, the integral of the error, derivative of the error constraints, and λ were considered in the proposed algorithm as tuning parameters to analyze the DC motor dynamic behaviors. The results showed that the proposed algorithm can be used to generate control actions taking into account the armature voltage and angular velocity limits. Also, results demonstrate that a controller subject to constraints can improve the electric vehicle DC motor dynamic; and at the same time it protects the motor from overvoltage.